The Inclusion of Minorities and the Sámi People in History Education in Finland - Kohvakka, Tanja (Åbo Akademi - Åbo Akademi University, 2024)
Finland is, and has always been, multicultural. It is home to various linguistic, cultural, ethnic, and religious minority groups as well as Indigenous Sámi people. However, this diversity, as well as the colonialist practices that the Sámi people have endured, are nearly invisible in history education. As a result, generations of schoolchildren have not received an adequate understanding of diversity in Finland. Against this premise, this dissertation examines the representation of minorities and Indigenous Sámi people in Finnish history education in comprehensive education. For the purpose of forming a thorough understanding of the topic, it explores history education by focusing on three aspects: national core curriculum, school history textbooks, and history teachers’ views and practices in the classroom. This dissertation consists of four articles and a concluding synthesis. Each publication approaches the representation of minorities and Indigenous people from their unique angles. The dissertation is positioned at the intersections between many disciplines, such as education, minority research and sociology. It draws from a combination of different theoretical traditions, most notably from critical pedagogy and multicultural education. The study is based on three sets of data: 1) national core curriculum for basic education, 2) history textbooks used in comprehensive schools, and 3) interviews with history teachers. This is a multimethod study that combines critical content analysis and discourse analysis. The results indicate that the representation of minorities and Indigenous people depends on various aspects. The study argues that while the norms and values stipulated in the curriculum could potentially facilitate the inclusion of minorities and Sámi in history education, the subject-specific instructions for history education do not explicitly instruct teachers to include them in their teaching. The study argues that minorities and the Sámi are scarcely represented in textbooks. However, the analysis ...